PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJATERHADAP PRESTASI KERJA PEGAWAI PADA BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR INSPEKSI BANDUNG (2018) - Sak Khie; Gian Gantika (Sekolah Tinggi Manajemen IMMI, 2020)
This study aims in general to analyze the influence of Organizational Culture and Work Environment on Employee Work Achievement at Bank Rakyat Indonesia (Persero) Tbk Inspection Office Bandung. The research method used in this research is survey by using data collecting instrument / instrument in the form of questionnaire which previously been tested the validity and reliability of the instrument. As the target population is the employees of Bank Rakyat Indonesia (Persero) Tbk Inspection Office Bandung, which amounted to 56 people, the size of the sample used as much as the size of the population. The sampling technique used is Saturated Sampling. Data analysis technique used is simple and multiple regression analysis. Prior to data analysis, firstly tested requirements analysis, namely through normality test, homogeneity test, multicolinearity test, heteroscedasticity test, and autocorrelation test. Based on descriptive statistical analysis obtained: (1) Employee job performance included in high category; (2) Organizational culture is included in high category, and Employee work environment is high category. While the results of hypothesis testing: (1) Organizational culture has a positive and significant impact on employee performance in Bank Rakyat Indonesia (Persero) Tbk Inspection Office Bandung, with the influence of 82.3% and 17.7% influenced by other variables or factors; (2) The work environment of employees has a positive and significant impact on employee performance at Bank Rakyat Indonesia Tbk Inspection Office Bandung, with the influence of 97.1% and 2.9% influenced by variables or other factors; (3) Organizational culture and working environment of employees together have a positive and significant effect on employee performance at Bank Rakyat Indonesia (Persero) Tbk Inspection Office Bandung, with the influence of 99.1% and 0.9% influenced by variables or factors other.